Mobiltechnológiával támogatott kutatásalapú tanulás - Bónus Lilla; Korom Erzsébet (Szegedi Tudományegyetem Bölcsészet- és Társadalomtudományi Kar Szeged, 2022)
Learning supported by mobile technology is extremely popular today because these technologies can support learning in different contexts. Mobile phones, e-book readers, MP3 and portable media players, tablets, laptops, smartphones, and GPS receivers can be considered mobile technology. As it can be seen from this list, they are different IT devices that can be held in the hand. Since they are portable devices, they enable learning regardless of time and place. The learning and teaching processes realized with mobile technology are called mobile learning (m-learning). Not only the device but also the student and learning are mobile. In the 2000s, research was published in the international literature in which mobile technologies supported learning by supplementing inquiry-based learning (IBL). Mobile technologysupported inquiry-based learning (mIBL) offers potential opportunities to support different levels of inquiry and generate new types of research; it helps to arouse and maintain students’ curiosity and motivation; it connects formal school and informal natural science learning related to everyday life. Although the research results so far show that mobile technology provides adequate support for IBL learning processes, practical strategies, recommendations, and guidelines are needed for further development and appropriate educational application. This study reviews the characteristics and practical applications of mobile learning through mobile technologies, emphasizing the support of inquiry-based learning.
Keywords: Társadalomtudományok; Oktatástudomány